A 9-year neuropsychological report of a patient with LGI1-associated limbic encephalitis. Issue 7 (9th August 2019) - Zangrandi, Andrea; Gasparini, Federico; Marti, Alessandro; Bhalla, Rishi; Napoli, Manuela; Angelini, Damiano; Ghidoni, Enrico; Rizzi, Romana
ABSTRACT: Introduction : Anti-leucine-rich glioma-inactivated 1 limbic encephalitis (LGI1-LE) is an autoimmune disorder associated with antibodies to voltage-gated potassium channels (VGKC). It is a non-paraneoplastic and partially reversible encephalitis that can be diagnosed via serological testing. Untreated LGI1-LE can be associated with neurocognitive as well as neuropsychiatric sequelae. Here we report the neuropsychological and clinical profile of a patient with LGI1-LE following three different treatment approaches: plasmapheresis (PA), intravenous immunoglobulin (IVIG), and corticosteroids (CO). Method : We investigated our patient with 10 neuropsychological evaluations obtained over a 9-year follow-up period. Multiple MRI scans, EEG recordings, neurological examinations, and serum tests were also obtained. Results : The neurocognitive profile of our patient was characterized by long-term memory impairment (verbal and visual-spatial), and deficits in aspects of executive functioning and language. Neuropsychiatric symptoms of depression and anxiety were noted intermittently. Conclusions : Non-specific treatment prior to diagnosis had marginal effects on neurocognitive profile, neuropsychiatric symptoms, or control of epileptic seizure. In contrast, specific treatments for LGI1-LE following diagnosis resulted in neurocognitive improvement and epileptic control. Among the three treatments, IVIG and CO had the most beneficial impact on neurocognitive status, likely due to the continuity of administration.